2015
DOI: 10.1185/03007995.2015.1006356
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of aripiprazole once-monthly in patients with schizophrenia

Abstract: Findings from PK data, PK simulations, and clinical studies all support that 400 mg is the appropriate initiation dose of AOM for patients with schizophrenia. When switching to oral aripiprazole before initiating AOM 400, tapering the prior oral antipsychotic while titrating up the oral aripiprazole dose (target dose 10-30 mg/d) over >1 to 4 weeks may be an effective strategy. The efficacy, safety, and tolerability of AOM 400 were comparable regardless of whether patients were previously stabilized on oral ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…This earlier study is of particular relevance because pharmacokinetic data indicate that the first injection of AOM 400 should be accompanied by an overlap with an oral antipsychotic. 20 In the acute study reported here, patients in the AOM 400 group took oral aripiprazole for the first 2 weeks of the study; thus, the influence of oral aripiprazole on the rapid effects observed in this post hoc analysis must be considered. 14 …”
Section: Discussionmentioning
confidence: 98%
“…This earlier study is of particular relevance because pharmacokinetic data indicate that the first injection of AOM 400 should be accompanied by an overlap with an oral antipsychotic. 20 In the acute study reported here, patients in the AOM 400 group took oral aripiprazole for the first 2 weeks of the study; thus, the influence of oral aripiprazole on the rapid effects observed in this post hoc analysis must be considered. 14 …”
Section: Discussionmentioning
confidence: 98%
“…In these and other key phase III studies, 90% of patients across studies who were initiated on the AOM 400 mg dose remained on that dose throughout, and rates of discontinuation due to lack of efficacy were in the order of 2%–10% [55, 6264]. As well as confirming 400 mg as an effective, safe and well tolerated initial dose in schizophrenic patients, Raoufinia et al demonstrated that the efficacy, safety and tolerability of AOM 400 in patients who were stabilized with oral aripiprazole for 2 weeks after the 1st injection of once-monthly aripiprazole was consistent regardless of whether patients were previously stabilized on oral aripiprazole 10 or 30 mg/day [64].…”
Section: Introductionmentioning
confidence: 99%
“…Error bars denote the 10th and 90th percentiles. Dashed horizontal lines represent the therapeutic window (i.e., the median simulated C min,ss for oral aripiprazole 10 mg/d [94.0 ng/mL] and the 75th percentile of the simulated C max,ss for oral aripiprazole 30 mg/d [534 ng/mL]) based on population pharmacokinetic (PK) simulations of once-daily oral aripiprazole (Raoufinia et al, 2015). Points represent individual outliers below the 10th and above the 90th percentiles.…”
Section: Resultsmentioning
confidence: 99%
“…A 24-week, open-label, parallel-arm, multiple-dose study in adult patients with schizophrenia stabilized on oral aripiprazole (n=41) evaluated the pharmacokinetics (PK), safety, and tolerability of 3 different doses of aripiprazole once-monthly (200, 300, and 400 mg) with concomitant oral aripiprazole (10 mg/d) for the first 14 days following the initial gluteal injection (Mallikaarjun et al, 2013). The PK data and clinical studies supported 400 mg as the starting and maintenance dose of aripiprazole once-monthly gluteal injection (Raoufinia et al, 2015). The mean (SD) steady state maximum concentration (C max,ss ) of aripiprazole once-monthly 400 mg (316 [160] ng/mL) (Mallikaarjun et al, 2013) was comparable with the C max of oral aripiprazole 20 to 30 mg/d (range, 393–452 ng/mL) (Mallikaarjun et al, 2004), and the trough steady-state concentration (C min,ss ; mean [SD], 212 [113] ng/mL) (Mallikaarjun et al, 2013) was similar to the steady-state C min of oral aripiprazole 15 to 20 mg (mean, 214 ng/mL; interquartile range, 124–286 ng/mL) (Kirschbaum et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation